Processo de criação artística e itinerários pedagógicos: reflexões sobre experiência na Escola Estadual Professor Ângelo Gosuen (Franca/SP) - Lopes Filho, Mauricio Oliver (2023)
The work is a result of teaching experience in basic education and training itineraries, contextualizing learning in contemporary times of students in the 1st year of high school at the Professor Angelo Gosuen State School, in the municipality of Franca, São Paulo, thus aiming at an integration knowledge and artistic practices in Art classes. The teacher, as a mediator of a formative teaching process, can encourage a creative process, giving freedom to students, in order to create a basis for structuring strategies for a project or development of didactic activities. The proposed path observes the idea of experience highlighted in Dewey (2010) and Larosa (2017, 1013) and in dialogues with contemporary artistteachers (BASSANI, 2018; COLLI, 2018) and essential references in the field of art, such as ALBANO (2013), BARBOSA (2012), OSTROWER (2013, 2012) and REY (2002). A path of construction is observed as a spiral proposal for the production of knowledge anchored in the critical idea of educational processes in favor of the artistic development of high school students in processes of itinerances and changes in pedagogical directions, in line with critical perspectives of educational processes based on Freire (2002, 2001), Morin (2013) and Mosé (2013) and in the legal guidelines in force (BRASIL, 2018; SÃO PAULO, 2021, 2020, 2008).